ASHRAE design guide for natural ventilation. (ASHRAE, 2020)
"ASHRAE Design Guide for Natural Ventilation assists owners, architects, engineers, facilities personnel, and building design professionals in exploring the feasibility of natural ventilation for their building project during the early phases of design"--